Performance-based seismic design of moment resisting steel frames: Adaptive optimisation framework and optimum design load pattern - Moghaddam, Hassan; Hajirasouliha, Iman; Hosseini Gelekolai, Seyed Mojtaba (Structures (Oxford), 2021)
In this study, a performance-based optimisation framework is proposed for optimal cross-sectional distribution of steel moment resisting frames (MRFs) subject to earthquake excitations. For the first time, the concept of uniform distribution of damage (UDD) is adopted for the complex optimisation of moment resisting steel frames under dynamic earthquake excitations. To enhance the computational efficiency of the optimisation process, a novel adaptive algorithm is proposed, where the power functions change based on the demand to capacity ratio of the structural elements. The framework is then used for optimisation of 3, 5, 7, 10 and 15-storey steel MRFs under a set of representative earthquake records. Maximum plastic rotations and strength-based demand to capacity ratios are considered as the main performance parameters for deformation-controlled and force-controlled members, respectively. The results indicate that the proposed method is very efficient at improving the seismic performance of the designed structures in only a few steps by satisfying all the prescribed performance targets. It is shown that, for the same performance level, the optimum design frames require up to 38% less structural-weight compared to their code-based design counterparts. The average storey shear force distributions of the optimum frames under the design spectrum-compatible earthquakes are then used to obtain more efficient lateral load patterns for seismic design of steel MRFs. It is shown that by adopting the proposed load pattern in the conventional seismic design process, the frames exhibit significantly (up to 70%) less global damage compared to the similar frames designed based on code suggested load pattern.